Język – tożsamość – komunikacja - Hofmański, Wojciech (Slavia Occidentalis, 2015)
This article discusses relation between language awareness, identity and multilingualism. Notion of bilingualism can be interpreted in many different ways – depending on research perspective (sociological, psychological, pragmalinguistic etc.). The most recent research (thanks tneuropsychological instruments) shows relatively objective view of this phenomenon. In this way, it is possible to separate natural bilingualism from (even perfect!) knowledge of foreign language – and double (lingual) identity from efficient exploitation of new, second languaculture.